Hepcidin antagonists for potential treatments of disorders with hepcidin excess - Poli, Maura; Asperti, Michela; Ruzzenenti, Paola; Regoni, Maria; Arosio, Paolo (Frontiers in Pharmacology, 2014)
The discovery of hepcidin clarified the basic mechanism of the control of systemic iron homeostasis. Hepcidin is mainly produced by the liver as a propeptide and processed by furin into the mature active peptide. Hepcidin binds ferroportin, the only cellular iron exporter, causing the internalization and degradation of both. Thus hepcidin blocks iron export from the key cells for dietary iron absorption (enterocytes), recycling of haemoglobin iron (the macrophages) and the release of storage iron from hepatocytes, resulting in the reduction of systemic iron availability. The BMP/HJV/SMAD pathway is the major regulator of hepcidin expression that responds to iron status. Also inflammation stimulates hepcidin via the IL6/STAT3 pathway with a support of an active BMP/HJV/SMAD pathway. In some pathological conditions hepcidin level is inadequately elevated and reduces iron availability in the body, resulting in anemia. These conditions occur in the genetic Iron Refractory Iron Deficiency Anemia (IRIDA) and the common Anemia of Chronic Disease (ACD) or Anemia of Inflammation. Currently, there is no definite treatment for ACD. Erythropoiesis stimulating agents and intravenous iron have been proposed in some cases but they are scarcely effective and may have adverse effects. Alternative approaches aimed to a pharmacological control of hepcidin expression have been attempted, targeting different regulatory steps. They include hepcidin sequestering agents (antibodies, anticalins and aptamers), inhibitors of BMP/SMAD or of IL6/STAT3 pathway or of hepcidin transduction (siRNA/shRNA) or ferroportin stabilizers. In this review we summarized the biochemical interactions of the proteins involved in the BMP/HJV/SMAD pathway and its natural inhibitors, the murine and rat models with high hepcidin levels currently available and finally the progresses in the development of hepcidin antagonists, with particular attention to the role of heparins and heparin sulphate proteoglycans in